A new species of Afrodiaphanes Geisthardt, 2007 (Coleoptera, Lampyridae), the first firefly described from the Central African Republic - Fanti, Fabrizio; Pankowski, Maximilian G. (Zootaxa, 2022)
A new species of firefly, Afrodiaphanes pulcher sp. nov., is described, diagnosed and illustrated. This is the first species of Afrodiaphanes described from the Central African Republic as well as the first firefly described from this nation.